INTEGRITAS INTEGRITAS PENDIDIKAN KARAKTER DAN ETIKA BERBAHASA DALAM PEMBELAJARAN BAHASA INDONESIA : Penerapan integrasi Pendidikan karakter dan etika berbahasa dalam pembelajaran Bahasa indonesia. Impplementasi Penerapan Integrasi Pendidikan Karakter dan Etika Berbahasa Dalam Pembelajaran Bahasa Indonesia - Moh Tabarok; Qurratul Aini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is an important element in human life. Character education is laid as the foundation for creating a society with noble, ethical, moral, civilized and civilized character based on the Pancasila philosophy. The use of degrading language and words is widespread and popular among students at all levels of education. The method used in this research is qualitative with descriptive analysis. Data collection techniques are observation, interviews and documentation. Data is processed through data reduction, data presentation and drawing conclusions. The results of this research show that the integration of character education and language ethics in class VI Indonesian language learning at MIS Nurul Hikmah Pamekasan Madura teachers make lesson plans first. The core part of the RPP includes: The teacher selects texts or reading materials that contain values that shape students' good character. After reading, students are invited to discuss the values contained in it, the teacher guides students to reflect on how the values that shape student character and language ethics are reflected, and finally, students are asked to write reflectively about their experiences in applying these values. -values in stories and language ethics in everyday life.